Phosphine–Stibine and Phosphine–Stiborane peri-Substituted Donor–Acceptor Complexes - Jan U. Bergsch; Alexandra M. Z. Slawin; Petr Kilian; Brian A. Chalmers (Molbank, 2023)
Two novel Sb(III) and Sb(V) peri-substituted acenaphthene phosphorus−antimony compounds were prepared. The Sb(III) compound, 1, was prepared via reacting the organolithium precursor with dichloro(p-tolyl)Stibine, and 2 was prepared by the chlorination of 1. Both 1 and 2 were characterized by multinuclear (1H, 13C and 31P) NMR spectroscopy, and their molecular structures resolved by single-crystal X-ray diffraction. Both compounds show a dative P−Sb interaction with the antimony being the acceptor group in both cases owing to its Lewis acidity.